2015
DOI: 10.1093/infdis/jiv176
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Breath Specimens for Biomarkers ofPlasmodium falciparumInfection

Abstract: Currently, the majority of diagnoses of malaria rely on a combination of the patient’s clinical presentation and the visualization of parasites on a stained blood film. Breath offers an attractive alternative to blood as the basis for simple, noninvasive diagnosis of infectious diseases. In this study, breath samples were collected from individuals during controlled malaria to determine whether specific malaria-associated volatiles could be detected in breath. We identified 9 compounds whose concentrations var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 31 publications
(35 reference statements)
2
75
3
Order By: Relevance
“…For example, during the analysis of breath samples of Plasmodium falciparum-infected volunteers, acetone was one of the nine VOCs whose level varied significantly over the course of malaria [220]. Unfortunately, the correlation between parasitemia and breath acetone was not investigated [220]. Fink et al examined VOC profile during sepsis, endotoxemic shock, and hemorrhagic shock in rats using ion mobility spectrometry, and measured decreasing acetone and 3-pentanone concentrations during endotoxemic shock and sepsis [221].…”
Section: Infectionsmentioning
confidence: 99%
“…For example, during the analysis of breath samples of Plasmodium falciparum-infected volunteers, acetone was one of the nine VOCs whose level varied significantly over the course of malaria [220]. Unfortunately, the correlation between parasitemia and breath acetone was not investigated [220]. Fink et al examined VOC profile during sepsis, endotoxemic shock, and hemorrhagic shock in rats using ion mobility spectrometry, and measured decreasing acetone and 3-pentanone concentrations during endotoxemic shock and sepsis [221].…”
Section: Infectionsmentioning
confidence: 99%
“…Breath73 Breath88 compounds (thioethers) in the GC-MS data, which were previously shown to increase in volunteers undergoing CHMI with P. falciparum as infection progresses [3]. The RT of these early-eluting peaks can vary for more than 1 min, which is much larger than the duration of the individual peak.…”
Section: Generating Training and Validation Datamentioning
confidence: 98%
“…For recurrent layers two and three, the output from the previous layer is used as the input. Mass spectrum at the time of peak maximum 3 Chromatograph segment -log scale Retention Time (min) Truth Figure S14: Alignment outcome for the data set Breath115 using the best performing network from model C. For this network, the true positive rate was 0.992 and the false positive rate was 0.004. (a) Chromatographic image: each horizontal position is a single sample and the points are plotted at the peak retention times.…”
Section: S17 Future Workmentioning
confidence: 99%
“…The concentrations of these compounds varied significantly as the disease progressed. Following antimalarial drug treatment, parasite clearance correlated strongly with a decline in VOC levels [60]. Notably, another recent study found that blood cultures of E. coli and S. aureus yielded different VOC profiles before and after exposure to gentamicin or flucloxacillin, demonstrating that antibiotic susceptibility status can also be rapidly evaluated by VOC analysis [61].…”
Section: Blood Infectionsmentioning
confidence: 99%